In‐situ nano‐engineering of amorphous MoS2 nanosheets with carbon dots for enhanced supercapacitor performances. (27th July 2022) - Panda, Prajnashree; Mishra, Ranjit; Barman, Sudip
Summary: Amorphous materials have snatched special attention for electrochemical energy storage applications owing to the presence of plenty of activate sites for energy storage. Herein, we report the microwave‐assisted‐hydrothermal synthesis of amorphous MoS2 with some 1T phase and in‐situ ‐ nano‐engineering with C‐dots for energy storage application. The specific capacitance (Cs ) of a‐MoS2 /C‐dots was found to be 1368 F g −1 (at 1 A g −1 ), which is ∼ 2.9 and 1.65 times higher than a‐MoS2 (without C‐dots) and crystalline c‐MoS2 /C‐dots. Capacitance is also strongly dependent on synthesis methods: Cs of a‐MoS2 /C‐dots is 2.15 times higher than h‐MoS2 /C‐dots produced by the normal‐hydrothermal method. The asymmetric supercapacitor was designed using a‐MoS2 /C‐dots as cathode and activated‐carbon as anode showing Cs 180.82 F g −1 at a maximum potential of 1.5 V. Energy density (ED) of 56.5 W h kg −1 at a power density (PD) of 750 W kg −1 with excellent capacitance retention was observed. The high Cs of a‐MoS2 /C‐dots can be attributed to amorphous MoS2, formation of metallic 1T phase, good charge transport, and strong catalyst support interaction. This synthesis and in‐situ nano engineering method of MoS2 may provide a promising technique for developing a high‐performance supercapacitor for energy storage applications. Abstract : Amorphous MoS2 /C‐dots are prepared by microwave‐assisted‐ hydrothermal method for energy storage application. The high electrochemical performance of MoS2 /C‐dots can be attributed to the amorphous MoS2, presence of some 1T phase, and in‐situ‐nano‐engineering of MoS2 with C‐dots. The specific capacitance of a‐MoS2/C‐dots was found to be 1368 F g −1 at 1 A g −1 current density with high cyclic stability.